Adiponectin suppresses colorectal carcinogenesis under the high-fat diet condition. Issue 11 (1st August 2008) - Fujisawa, T; Endo, H; Tomimoto, A; Sugiyama, M; Takahashi, H; Saito, S; Inamori, M; Nakajima, N; Watanabe, M; Kubota, N; Yamauchi, T; Kadowaki, T; et al.
Abstract : Background and aims: The effect of adiponectin on colorectal carcinogenesis has been proposed but not fully investigated. We investigated the effect of adiponectin deficiency on the development of colorectal cancer. Methods: We generated three types of gene-deficient mice (adiponectin-deficient, adiponectin receptor 1-deficient, and adiponectin receptor 2-deficient) and investigated chemical-induced colon polyp formation and cell proliferation in colon epithelium. Western blot analysis was performed to elucidate the mechanism which affected colorectal carcinogenesis by adiponectin deficiency. Results: The numbers of colon polyps were significantly increased in adiponectin-deficient mice compared with wild-type mice fed a high-fat diet. However, no difference was observed between wild-type and adiponectin-deficient mice fed a basal diet. A significant increase in cell proliferative activity was also observed in the colonic epithelium of the adiponectin-deficient mice when compared with wild-type mice fed a high-fat diet; however, no difference was observed between wild-type and adiponectin-deficient mice fed a basal diet. Similarly, an increase in epithelial cell proliferation was observed in adiponectin receptor 1-deficient mice, but not in adiponectin receptor 2-deficient mice. Western blot analysis revealed activation of mammalian target of rapamycin, p70 S6 kinase, S6 protein and inactivation of AMP-activated protein kinase in the colon epithelium of adiponectin-deficient mice fed with high-fat diet. Conclusions: Adiponectin suppresses colonic epithelial proliferation via inhibition of the mammalian target of the rapamycin pathway under a high-fat diet, but not under a basal diet. These studies indicate a novel mechanism of suppression of colorectal carcinogenesis induced by a Western-style high-fat diet.